Reinserção no trabalho: estudo do fenômeno em uma Instituição Federal de Ensino Superior - Macedo, Danielle Constância Felício (2019)
The present study chose as central theme the reinsertion in the work of federal public servants with some type of restriction in their work activities due to health reasons. Restricion of work permeates the complex spectrum of a person’s abilities and incapacities to perform their duties within the scope of work. The aim of this work was to investigate in the light of the theoretical references of ergology, the ergonomics of the activity and in accordance with the assumptions of the International Classification os Disability, Funcionality and Heatlh (CIF), the process of reinsertion of serves with labor restrictions. The specific objectives involved: (a) to investigate the presence and characterization of complaints related to work problems documented in the records of server of a Federal Higher Education Institution in Brazil’s Southeast Region, considering the chapters of ICD 10 that generae a greater number of leave days of work in 2015; (b) describe the profile of these servers with regard to: sex, age, marital status, schooling occupation, time of absence, working time in the institution, presence of comorbidities, presence of restrict report, reference to removal, besides number of work-related complaints; (c) describe the process of reinsertion of federal public servants with work restrictions from the perspective of servants with reports, colleagues and heads of persons in this condition; (d) explore in the light of ergology the dramatic use of self, the debates of norms, values and knowledge in the scenario of labor reintegration, identifying points of articulation and contribution of knowledge of the CIF and the ergonomics of the activity; (d) identify, in accordance with the CIF, the facilitators and perceived barriers to the process of reinsertion of federal public servants with work restrictions from the perspective of servants with reports, colleagues and heads of persons in that condition; (e) propose the from “Work Performance Analysis” for the complementary evaluation of the from “Work Performance Analysis” for the complementary evaluation of the worker’s performance against the demands of his/her work activity; (f) present the implementation of functional rehabilitation actions in a Federal Higher Education Institution in Brazil’s Southeast Region. The thematic attitudes and interpersonal relationships were the ones with the highest density found in the results of this thesis. Situations were identified in which both the health license and the request for removal revealed a complex institutional symptom of insufficient material and human resources for a resolute and early approach to the suffering processes and work-related grievances manifested by the employees. The servers with a restrictive report had a higher number of complaints related to work and a greater number of days of leave to treat their own health. In this multifaceted context of work realities, the debate about the demands of productivity and work capacity mobilizes TS professionals to analyze strategies to overcome the challenges experienced in the relevant, safe and responsible maintenance of people with some kind of work restriction in the productive system .